Cardiovascular safety of lumiracoxib: A meta-analysis of all randomized controlled trials ≥1 week and up to 1 year in duration of patients with osteoarthritis and rheumatoid arthritis - Matchaba, Patrice; Gitton, Xavier; Krammer, Gerhard; Ehrsam, Elena; Sloan, Victor Schorr; Olson, Melvin; Mellein, Bernhard; Hoexter, Godehard; Orloff, John; Garaud, Jean-Jacques (Clinical therapeutics, 2005)
Abstract The cardiovascular (CV) safety of non-steroidal anti-inflammatory drugs (NSAIDs) and selective cyclooxygenase-2 inhibitors has been the subject of considerable debate. The objective of this study was to determine the risk of CV events with lumiracoxib by meta-analysis of all completed, randomized controlled trials (RCTs) of ≥1 week and up to 1 year in duration of patients with osteoarthritis and rheumatoid arthritis. The Novartis Lumiracoxib Clinical Trial Database, which includes all clinical studies conducted to date with lumiracoxib, was reviewed. Data were extracted from RCTs of ≥1 week and up to 1 year in duration, the maximum study duration; 34,668 patients were included in standard and cumulative meta-analyses. Twenty-two RCTs of lumiracoxib 100 to 1200 mg daily were identified; 22,781 patients were included in 1-year trials. Mean age of the patients was 61.5 years and 74% were female. More than 50% of the patients in these studies had hypertension at baseline and 6% had diabetes. Parameters analyzed were the Antiplatelet Trialists' Collaboration (APTC) composite CV end point of myocardial infarction (MI), stroke (ischemic and hemorrhagic), and CV death; MI alone; and stroke alone. Twenty-one of the 22 RCTs have been published. For all 3 parameters, relative risk (RR) was calculated versus non-naproxen NSAIDs, naproxen, and placebo. The results were as follows: for the APTC end point versus non-naproxen NSAIDs: RR 0.83, 95% CI, 0.46–1.51; versus naproxen: RR 1.49, 95% CI, 0.94–2.36; versus placebo: RR 1.08, 95% CI, 0.41–2.86; for MI alone versus non-naproxen NSAIDs: RR 0.80, 95% CI, 0.28–2.25; versus naproxen: RR 1.69, 95% CI, 0.82–3.48; versus placebo: RR 1.27, 95% CI, 0.25–6.56; and for stroke alone versus non-naproxen NSAIDs: RR 0.91, 95% CI, 0.35–2.35; versus naproxen: RR 1.42, 95% CI, 0.70–2.91; versus placebo: RR 0.59, 95% CI, 0.13–2.74. Cumulative meta-analyses of lumiracoxib versus all comparators (placebo, diclofenac, ibuprofen, celecoxib, rofecoxib, and naproxen) did not find any significant differences in APTC, MI alone, or stroke alone. This meta-analysis of 34,668 patients receiving ≥1 week and up to 1 year of treatment found no evidence that lumiracoxib was associated with a significant increase in CV risk compared with naproxen, placebo, or all comparators (placebo, diclofenac, ibuprofen, celecoxib, rofecoxib, and naproxen).